Close Mapping of St. Olav’s Pilgrimage Path Through Gudbrandsdal Norway: Probabilities of a Designed, Land Surveyed Concept of a Large-Scale Christianised Landscape - Doxtater, Dennis (The international journal of religious tourism and pilgrimage, 2023)
This exercise in Norway ‘close-maps’ accurate, existing geometries between thirty-two latitude / longitude points of mostly medieval churches and other sites on the major pilgrimage path through Gudbrandsdal to Trondheimsfjord where the martyr St.Olav was venerated. Site data and basic path routes are taken from the Pilegrimsleden website, popular today with religious or recreational tourists. The inclusion of the largest prehistoric monumental mound in Scandinavia as an important early stop on the pilgrimage provides the first clue to the eventual mapping of a large-scale ‘system’ of land surveyed patterns. This symbolic anchor in the south, is connected to likely ancient religious sites to the north in Trondheimsfjord where St. Olav was killed in battle. Discovered are several early church sites key to site integration but not included as part of today’s pilgrim path. The Gudbrandsdal route appears to have been laid out earlier than the smaller volume, overlapping, Østerdal path immediately to the east. To distinguish formally designed geometric large-scale patterns from random phenomena, test areas are created where equal numbers of random points replace the existing. Combinations of three-point alignments, cardinal (N-S. E-W) alignments between two points, and right-angle relationships between three points are tested at increasing complexities of combination at accuracies of 0.06° angular deviation or less, mostly around 0.04°. The ‘systemic’ map pattern that tests show to be highly probable as designed and land surveyed - occurring about 1 in 100,000 random sets - shows considerable overlap with the Gudbrandalsleden map created by the Norwegian website, but variation and omission of important sites occur. The conclusion raises final questions about the value of this real, close-map information to the modern ‘pilgrim’, and to more academic historians and archaeologists. Can today’s path experience be heightened by the creation of a more holistic and symbolic concept of modern Norwegian landscape, this is considered together with insights into how historically such a concept may have moderated civil conflict and integrated an imported book-based religion with ancient Norse ritual practice?